Hbr's 10 must reads on design thinking with featured article "design thinking" by tim brown - Review, Harvard Business; Govindarajan, Vijay; Nooyi, Indra; Christensen, Clayton M.; Brown, Tim.; Recorded Books, Inc. ([S.l.] : Harvard Business Review Press, 2020)
Use design thinking for competitive advantage. If you read nothing else on design thinking, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you use design thinking to produce breakthrough innovations and transform your organization. This book will inspire you to: -Identify customers' "jobs to be done" and build products people love -Fail small, learn quickly, and win big -Provide the support design-thinking teams need to flourish -Foster a culture of experimentation -Sharpen your own skills as a design thinker -Counteract the biases that perpetuate the status quo and thwart innovation -Adopt best practices from design-driven powerhouses This collection of articles includes "Design Thinking," by Tim Brown; "Why Design Thinking Works," by Jeanne M. Liedtka; "The Right Way to Lead Design Thinking," by Christian Bason and Robert D. Austin; "Design for Action," by Tim Brown and Roger L. Martin; "The Innovation Catalysts," by Roger L. Martin; 'Know Your Customers' 'Jobs to Be Done,'" by Clayton M. Christensen, Taddy Hall, Karen Dillon, and David S. Duncan; "Engineering Reverse Innovations," by Amos Winter and Vijay Govindarajan; "Strategies for Learning from Failure," by Amy C. Edmondson; "How Indra Nooyi Turned Design Thinking into Strategy," by Indra Nooyi and Adi Ignatius, and "Reclaim Your Creative Confidence," by Tom Kelley and David Kelley. HBR's 10 Must Reads paperback series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their companies, should look no further. HBR's 10 Must Reads series focuses on the core topics that every ambitious manager needs to know: leadership, strategy, change, managing people, and managing yourself. Harvard Business Review has sorted through hundreds of articles and selected only the most essential reading on each
Intro -- Title Page -- Copyright -- Contents -- Design Thinking -- Why Design Thinking Works -- The Right Way to Lead Design Thinking -- Design for Action -- The Innovation Catalysts -- Know Your Customers' "Jobs to Be Done" -- Engineering Reverse Innovations -- Strategies for Learning from Failure -- How Indra Nooyi Turned Design Thinking into Strategy -- Reclaim Your Creative Confidence -- About the Contributors -- Index
Title from resource description page (Recorded Books, viewed July 20, 2020).
OCLC control number change
Keywords: Business; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; Business; elektronické knihy; electronic books